The thalassaemia trait in an English family - Roberts, P. D. (1963)
Nine cases of the thalassaemia trait are described in an English family. The problem of distinguishing these cases from those of the common hypochromic anaemias by simple laboratory tests is discussed. Iron-resistant hypochromic anaemia in people of British ancestry may be caused by the thalassaemia trait. Such cases have been reported by Bywaters (1938), Israëls, Suderman, and Hoogstraten (1955), Israëls and Turner (1955), and Havard, Lehmann, and Bodley Scott (1958). Dacie (1960) mentions similar cases and Callender, Mallet, and Lehmann (1961) recently described the finding of 25 cases in three English families.